Finite Element Methods Problem 6.2 : the six-step FE approach for a truss system - Jones, Simon (McGraw-Hill's AccessEngineering., 2022)
The six-step finite element approach is employed to solve a six-degree-of-freedom 2D truss problem. The inclined truss element is introduced.